PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA UMKM CHEESE STICK ALFAN - Astuti, Rika (Universitas Siber Indonesia, 2024)
Cheese Stick Alfan is one of the micro, small and medium businesses, which until now the production and sales process is still carried out by buyers who come directly. There are still many weaknesses found in the sales process at Cheese Stick Alfan, for example, they have not used technology. a tool to market a product they will sell. so that business actors can sell their products using the existing WEBSITE to cities or villages that are connected to the internet. Therefore, Cheese Stick Alfan requires an information system such as e-commerce to better identify the products being sold and provide convenience. The purpose of this writing is to give even better results, at the Alfan Cheese Stick store, by implementing the concept in the form of a web-based application. The design of this sales system will use the waterfall method and the end result is a web-based application which is also expected to help the sales process at the Cheese Stick Alfan store.